Psychosocial risk factors for injury in performing artists: A scoping review of screening and assessment instruments - Róisín Cahalan; Caoimhe Barry Walsh; Orfhlaith Ni Bhriain; Breandán de Gallaí; Hannah Fahey de Brún; Michele Pye; Rose Schmieg (PLoS ONE, 2026)
The performing arts is a diverse collection of disciplines, sharing an elevated risk of injury related to an array of biopsychosocial risk factors. While screening for physical risk factors is common practice, and largely routine, psychosocial screening for injury in performance artists (PAs) is less well established. This scoping review aimed to systematically map the array of instruments used to screen for, or assess, psychosocial risk factors for injury in non-recreational adult performing artists (PA)s. Additionally, psychometric evaluations of each instrument in PA cohorts were reported where available. This scoping review was conducted in accordance with the Joanna Briggs Institute Evidence Synthesis guidelines. Twelve databases relating to performance, health, medicine, kinesiology, and sport were searched. Studies that investigated associations between psychosocial factors and injury in non-recreational (professional, pre-professional, full-time collegiate students, elite competitive) adult PAs were eligible. Fifty-one studies of 7,457 participants met the inclusion criteria (musicians: n = 4,505 (60.5%); dancers: n = 2,680 (35.9%); vocalists n = 225 (3.0%); circus performers: n = 47 (0.6%)). Most participants were professional PAs (n = 4,547 (61.0%)), followed by collegiate PAs (n = 1,424 (19.1%)), and mixed professional, pre-professional, elite competitive, and collegiate cohorts (n = 1,486 (19.9%)). Forty-five different psychosocial factors were identified across 90 distinct instruments. Stress, anxiety, depression and perfectionism were the factors most frequently investigated. Stress was commonly reported across all PA cohorts. The reliability of just 19 (21%) instruments was established for the target cohort. Many other instruments were valid/reliable in patient, sporting or general population cohorts, but untested in PAs. A common link between many psychosocial risk factors and injury in non-recreational adult PAs was identified. Screening programmes should incorporate comprehensive evaluations of these factors. Instruments appropriate for the cohort investigated should be used where available. The development and/or validation of instruments for use across all PAs for common risk factors should be considered.